Odpowiedź :
Odpowiedź:
x = -8/3
Szczegółowe wyjaśnienie:
[tex]\dfrac{2x+7}{x+1}=-1[/tex]
Na początku określamy dziedzinę wyrażenia:
[tex]\mathbb{D}:\\x+1\neq0\qquad|-1\\x\neq-1\\\\\huge\boxed{\mathbb{D}=\mathbb{R}-\{-1\}}[/tex]
[tex]\dfrac{2x+7}{x+1}=\dfrac{-1}{1}[/tex]
mnożymy na krzyż
[tex]1(2x+7)=-1(x+1)\\2x+7=-x-1\qquad|-7\\2x=-x-8\qquad|+x\\3x=-8\qquad|:3\\\boxed{x=-\dfrac{8}{3}}\in\mathbb{D}[/tex]
Odpowiedź:
Szczegółowe wyjaśnienie:
2x+7/x+1=-1 /*(x+1)
2x+7= -x-1
2x+x=-1-7
3x=-8/:3
x=-8/3= -2 2/3